(untitled) (Baghdad Science Journal, 2013)
Cinnamon plant is considered one of important medicinal plants because it is rich with many active compounds. This research is aimed to study possible effects of extract in culture media of Gardenia jasmenoides. Alcoholic extract was prepared from the bark of cinnamon at different concentrations (0.0, 1.0, 2.0) mg/L, then added to culture media to notice the effect of these concentrations on the growth and development of tissues and organs of Gardenia jasmenoides Ellis in vitro. Results showed the positive effect of increasing callus fresh weight and shoot proliferation from single nodes with presence of plant regulators, 5.0 mg/L Naphthalene acetic acid (NAA) and 3.0 mg/L Benzyl adenine (BA). Results showed that extract has a slight effect on root formation with the presence of plant regulators or when it is alone.